SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DENGAN METODE ELECTRE (ELIMINATION ET CHOIX TRADUISTANT LA REALITE) STUDI KASUS: KECAMATAN SELESAI - Khairunnisa Harahap; Akim MH Pardede; Tio Ria Pasaribu (STMIK KAPUTAMA, 2021)
Program Keluarga Harapan (PKH) is an intense social protection program on providing cash assistance to households that meet the criteria of the Program Keluarga Harapan (PKH). The goal of Program Keluarga Harapan (PKH) in the short term is to reduce the burden of KSM (Very Poor Families) while in the long term it is expected to break the poverty chain between generations, so that the next generation can get out of poverty and be more prosperous. Based on the results of this study proposed a decision support system with the METHOD ELECTRE (Elimination Et Choix Traduisant La Realite) which is one of the multi-criterion decision making methods based on the concept of outranking by using a paired comparison of alternatives based on each appropriate criteria. From the ELECTRE method, there is an alternative result that is less favourable, namely A1 with the result of 0, A2 with the result of 0, A3 with the result of 2, A2 with the result of 1 and A5 with the result of 4. Thus the A5 becomes the alternative with the highest value.